Use of Social Media in Crisis Communication in the Federal Government During COVID-19 Pandemic: Analysis of Responses Strategies - El Mouloudi, Mostapha (Université d'Ottawa / University of Ottawa, 2022)
Social media has become a prime tool in communicating during crises. Ongoing COVID-19 pandemic illustrates this trend strongly with the Canadian government conveying messaging through many platforms. In this thesis, we aimed to explore how Public Health Agency of Canada (PHAC) and Health Canada (HC) communicate with Canadians through social media, namely Twitter. Based on insights from social media practices drawn from work by Wendling et al. (2013); Lin et al. (2016) and from social mediated crisis communication theory of Austin et al. (2012), we sought to find what type of social media strategies adopted to execute crisis communication during COVID-19 pandemic. We also aimed at understanding to what extent these reflect the theoretical framework of the present study. To undertake this research, we opted for a mix of quantitative and qualitative analysis enabled by thematic analysis to identify categories of meaning and their trend. We found that social media strategies adopted by PHAC and HC have many aspects in common with the theoretical framework, yet they offer many nuances in practices driven mainly by the length of the crisis and the uncertainty it has caused. This thesis brings theory into practice by researching an ongoing crisis, gauging social media use practices against messaging strategies. It also calls on the need for updating theories and good practices in light of the outcomes of the COVID-19 crisis.
Keywords: crisis; crisis communication; social media; Government of Canada; government communication; risk society; uncertainty; misinformation; Twitter; preparedness; rules of engagement; emergency; public health; online interaction